Three most widely used gnss-based shoreline monitoring methods to support integrated coastal zone management policies - Goncalves, R.; Awange, Joseph (American Society of Civil Engineers, 2017)
Shoreline monitoring is essential for integrated coastal zone management (ICZM). It provides the necessary information needed to manage the settlement of coastal areas, establishes guidelines for management of socioeconomic activities within the coastal areas, provides information necessary for recovery actions of beach regeneration, and provides a reference baseline for studies related to climate change in coastal zones. Shoreline monitoring methods are largely dependent on goals, costs, implementation, and applicability. For monitoring of short coastal shorelines (e.g., tens to hundreds of kilometers), global navigation satellite system (GNSS)-based methods are emerging as low-cost approaches that offer rapid, weather-independent, and quickly updatable products that could benefit policy makers when high costs of traditional methods, such as photogrammetry and remote sensing, are of concern. However, various GNSS methods applicable to shoreline monitoring exist, making it difficult for decision makers to choose a suitable approach. Using a case study of the Pernambuco State ICZM in Brazil, this study evaluates three of the most commonly used GNSS-based shoreline monitoring methods, that is, relative kinematic (RK), real-time kinematic (RTK), and precise point positioning (PPP) methods. It also provides a comprehensive analysis of their strengths and limitations. The results highlight the issues and important considerations in choosing an economically viable GNSS method for mapping shoreline changes, particularly for supporting ICZM policies.